QUALITY ASSURANCE OF VARI-SOURCE HIGH DOSE RATE (HDR) BRACHYTHERAPY- REMOTE AFTER LOADER AND COST EFFECTIVENESS OF VARI-SOURCE HDR- BRACHYTHERAPY: NORI, ISLAMABAD EXPERIENCE - Ahmad, N.; Mahmood, H.; Jafri, S.R. A. (The Nucleus, 2020)
A quality control of Vari-Source high dose rate (HDR) remote after loading brachytherapy machine was carried out and the cost effectiveness of HDR brachytherapy machine was also evaluated considering the cost of ten Iridium-192 wire sources at Nuclear Medicine, Oncology and Radiotherapy Institute (NORI), Islamabad, Pakistan. A total number of 253 intracavitary insertions were done in 98 patients from October 1996 to May 2001. The results of the quality control tests performed during 1996 to 2001 were within the acceptable limits. The cost effectiveness of Vari-Source HDR brachytherapy machine was also evaluated. The average cost per patient was calculated as US 491. Small number of patients was treated as the machine was used for gynecologic malignancies only. The objective was to assess the quality control status of HDR brachytherapy machine on patient treatment day, source exchange day and periodic day (monthly basis). It was found that the cost per patient can be minimized if other type of cancer patients are also treated on Vari-Source HDR machine.